Economics - Samuelson, Paul A.; Nordhaus, William D. (New Delhi McGraw Hill Education, 2010)
Written by the best experts in the field, Economics is a book which is regarded as one of the finest works in contemporary economics. It has been divided into seven parts with a total of 31 chapters overall. The first part deals with the explanation of the basic concepts related to economics. This covers the concepts that form the core of economics, contemporary mixed economy, and the basic components of demand and supply. The second part broadly covers microeconomics, and includes chapters which deal with demand, supply, elasticity and its applications, product markets, demand and behavior of consumer, business organisation and production, etc. It also deals with perfectly competitive markets and its analysis, analysis and costs, monopoly, imperfect competition, the competition within some of those, and the economics which pertain to uncertainties.
Keywords: Commerce